TURN-TAKING STRATEGY: THE EFFECTIVE WAY TO IMPROVE STUDENTS’ SPEAKING SKILL - Paris, Atika Salman (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
The purpose of this research is to improve students’ speaking ability using a turn-taking strategy, The design of this research is classroom action research, this research uses two cycles, and each cycle has some stages, such as planning, acting, observing, and reflecting. The data analysis of this research used tests and observation. The result of this research is the students’ self-confidence was increased, the students’ communication was improved, and the students decreased their mother tongue use. It can be seen from the score of each test. Additionally, the score of the students increased in each cycle, in cycle 1 when the researcher do the speaking test, the student’s score was 73, which means that the students still got under the standard score. In cycle 2 the students’ score was 80, which means that the students got a high score. Thus, it can be concluded that the turn-taking strategy was an appropriate strategy to improve students’ speaking ability at MAN 1 Mataram.